Fluorescencing Behavior of Thin Solid Films Based on Polyelectrolyte-Surfactant Complex and Dye Molecules - Seliverstova, E.; Ibrayev, N.; Kudaibergenov, S. (Applied Polymer science, 2012)
This article is devoted to investigation of interaction between polycomplex and dye molecules assembled in fluorescent thin solid Langmuir-Blodgett (LB) films. Preparation procedure of organosoluble stoichiometric polycomplex based on cationic polyelectrolyte and anionic surfactant is described. Formation of mixed monolayers consisting of polyelectrolyte-surfactant complex (PSC) and dye molecules–Nile Red (NR) at water-air interface is shown. Assembling conditions of LB films based on PSC and NR are defined and the spectral-luminescent properties of obtained films are studied. It is shown that when nonamphiphilic NR and PSC are mixed the excellent monolayers formed, which can easily be transferred onto solid substrates by Langmuir-Blodgett method with a high transfer coefficient. Absorption and fluorescence spectra of mixed LB films reveal the formation of dimers and existence of monomers in LB films.
Keywords: polyelectrolytes; dyes/pigments; films; spectroscopy